1978
DOI: 10.1128/jb.135.1.124-132.1978
|View full text |Cite
|
Sign up to set email alerts
|

Post-Transcriptional Modifications of the Anticodon Loop Region: Alterations in Isoaccepting Species of tRNA's During Development in Bacillus subtilis

Abstract: Structural similarities of tRNA's were compared using three sets of isoaccepting species that had previously been shown to undergo significant changes in chromatographic elution properties as a function of developmental stage in Bacillus subtilis. Comparisons of the structures of the tRNA's were based on the composition oftheir modified nucleosides, comparisons of oligonucleotide elution profiles from RPC-5 columns, and two-dimensional electrophoretic fingerprint analysis of oligonucleotides. The tRNA's studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

1979
1979
1984
1984

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…The 2-D gel patterns of tRNA samples labeled during vegetative growth, sporulation, and outgrowth are stikingly simila. This result and reports that the alterations observed in at least four tRNA's (tRNALYO, tRNAT', tRNAPhe, and tRNATh") during sporulation are due to posttranscriptional modifications of vegetative tRNA's (2,15,21,37) strongly suggest that the same tRNA genes are transcribed at all stages of the B. subtilis life cycle.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…The 2-D gel patterns of tRNA samples labeled during vegetative growth, sporulation, and outgrowth are stikingly simila. This result and reports that the alterations observed in at least four tRNA's (tRNALYO, tRNAT', tRNAPhe, and tRNATh") during sporulation are due to posttranscriptional modifications of vegetative tRNA's (2,15,21,37) strongly suggest that the same tRNA genes are transcribed at all stages of the B. subtilis life cycle.…”
Section: Discussionsupporting
confidence: 54%
“…Investigations of mechanisms controlling bacterial spore development have involved an intense examination of the regulatory role that tRNA may play in this system (18,20,21,35). Sporulation in Bacillus subtilis is accompanied by significant qualitative and quantitative changes in at least eight iso-accepting tRNA species (37). The chromatographic changes for at least two tRNA species (tRNATYr and tRNALY8) are clearly the result of post-transcriptional tRNA modification (15,37).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The highly modified Q nucleoside, however, is a unique exception in that it is synthesized as the free Q base (queuine) which is then inserted into tRNA by a transglycosylase to replace guanine (Okada et al, 1979). Bacterial tRNAs normally are completely modified with respect to Q (Katze and Mosteller, 1976;Vold, 1978) but in eukaryotes tRNAs may exhibit a variable Q content depending on the developmental state and/or growth conditions (White et al, 1973;Katze, 1975). It has been shown that undermodified tRNAs containing guanine instead of queuine specifically appear in a variety of tumour cells (Okada et al, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…Completeness (or incompleteness) of post-transcriptional modifications of tRNAs, such as have been reported mainly in eukaryotes [5,47] (and references therein), may also be part of this tuning of the translation process. It is generally believed that this depends on alterations in the nutritional or the physiological state of the cell, but the meaning of such observations are relatively unclear.…”
Section: T6a May Not Be Strictly Required For Codon-anticodon Interacmentioning
confidence: 99%